An updated review of Chinese skullcap (Scutellaria baicalensis): Emphasis on phytochemical constituents and pharmacological attributes - Dilip Kumar Chanchal; Kuldeep Singh; Bharat Bhushan; Jitendra Singh Chaudhary; Shivendra Kumar; Ajit Kumar Varma; Neha Agnihotri; Akash Garg (Pharmacological Research - Modern Chinese Medicine, 2023)
Chinese Skullcap (Scutellaria baicalensis) is a traditional medicinal herb with a rich history of use in Traditional Chinese Medicine (TCM). This review aims to provide an updated overview of the phytochemical constituents and pharmacological attributes of Chinese Skullcap, shedding light on its potential therapeutic applications. A comprehensive search of scientific databases, including PubMed, Scopus, and Web of Science, was conducted to gather relevant literature published up to September 2023. Keywords such as ''Scutellaria baicalensis,'' ''phytochemicals,'' and ''pharmacological properties'' were used to identify pertinent studies. Chinese Skullcap was found to contain a diverse array of phytochemical constituents, including flavonoids, alkaloids, and terpenoids, with baicalin and baicalein being the most prominent bioactive compounds. These compounds have demonstrated a wide range of pharmacological activities, including anti-inflammatory, antioxidant, anti-cancer, neuroprotective, and hepatoprotective effects. Additionally, Chinese Skullcap has been investigated for its potential in treating various diseases, such as cancer, cardiovascular disorders, and neurodegenerative conditions. Chinese Skullcap represents a compelling avenue for future therapeutic development, emphasizing the ongoing need for scientific exploration and clinical investigation.